A 9-year-old-girl with Phelan McDermid Syndrome, who had been diagnosed with an autism spectrum disorder - Görker I; Gürkan H; Demir Ulusal S; Atlı E; Ikbal Atlı E (Balkan Journal of Medical Genetics, 2016)
Phelan McDermid Syndrome (PHMDS) (OMIM #606232), is a contiguous gene disorder resulting from deletion of the distal long arm of chromosome 22. The 22q13.3 deletions and mutations that lead to a loss of a functional copy of SHANK3 (OMIM *606230) cause the syndrome, characterized by moderate to profound intellectual disability, severely delayed or absent speech, hypotonia, and autism spectrum disorder (ASD) or ASD traits. In this study, we present the case of a 9-year-old girl who had earlier been diagnosed with an ASD. Our findings were a clinically mild intellectual disability, rounded face, pointed chin but no autistic findings. We learned that her neuromotor development was delayed and she had neonatal hypotonia in her history. A heterozygous deletion of MLC1, SBF1, MAPK8IP2, ARSA, SHANK3 and ACR genes, located on 22q13.33, was defined by multiplex ligation-dependent probe amplification (MLPA). Deletion of 22q13.3 (ARSA) region was confirmed by a fluorescent in situ hybridization (FISH) technique. The 22q13.3 deletion was found to be de novo in our patient, and she was diagnosed with PHMDS. We confirmed the 22q13.3 deletion and also determined a gain of 8p23.3-23.2 by array comparative genomic hybridization (aCGH). Fluorescent in situ hybridization was performed to determine whether the deletion was of parental origin and to identify regions of chromosomes where the extra 8p may have been located. The parents were found to be normal. The extra copy of 8p was observed on 22q in the patient. She is the first case reported in association with the 22q deletion of 8p duplications in the literature.